Posterior Reversible Encephalopathy Syndrome Associated with Tacrolimus in Cardiac Transplantation - Julián Alejandro Rivillas; Stephania Galindo-Coral; Francisco Arias-Mora; Juan David Lopez-Ponce de Leon; Noel Alberto Florez-Alarcón; Pastor Olaya-Rojas; Juan Esteban Gomez-Mesa (Case Reports in Cardiology)
Background. Neurological complications occur between 50 and 70% of patients with heart transplantation, including cerebrovascular events, infections, seizures, encephalopathy, and neurotoxicity due to pharmacological immunosuppression. Mortality associated with cerebrovascular complications is 7.5% in the first 30 days and up to 5.3% after the first month and up to the first year after transplantation. Case Reports. Three heart-transplanted patients (2 men and 1 woman) treated with tacrolimus were identified. They presented with posterior reversible encephalopathy syndrome on days 5, 6, and 58 posttransplantation, respectively. In these reported cases, no sequelae were observed at 6 months follow-up. Conclusions. Posterior reversible encephalopathy syndrome as a neurological complication in patients with HT occurred early after the procedure. Early diagnosis and treatment might reduce the risk of serious complications and mortality.